Učinki vstopa tujega podjetja na tržno strukturo v državi gostiteljici - Zajc Kejžar, Katja (Naše gospodarstvo, 2008)
This paper examines the effects of foreign firm entry on market structure in a host country. Within a two-stage oligopolistic model in which a foreign firm decides how to enter the host-country market (export versus foreign direct investment), while two asymmetrical local firms decide on their exit/stay strategy, we show that foreign firm entry causes reallocation of market shares across firms within the industry and increases the probability of the exit of the least efficient firm in the host economy. The traditional expectation that the higher the degree of firm-heterogeneity in a host country the more likely is an entry via FDI and the exit of the least efficient local rival is confirmed only for the situation where there are no productivity spillovers.
Keywords: mednarodna trgovina; izvoz; tuje investicije; vplivi; učinki